2021
DOI: 10.1007/s11676-021-01346-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in temperature sensitivity of soil respiration in a larch forest in the Northern Daxing’an Mountains in Northeast China

Abstract: Temperature sensitivity of respiration of forest soils is important for its responses to climate warming and for the accurate assessment of soil carbon budget. The sensitivity of temperature (Ti) to soil respiration rate (Rs), and Q10 defined by e10(lnRs−lna)/Ti has been used extensively for indicating the sensitivity of soil respiration. The soil respiration under a larch (Larix gmelinii) forest in the northern Daxing’an Mountains, Northeast China was observed in situ from April to September, 2019 using the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[62] a high coefficient of determination (R 2 ) indicates high reliability and precision in the response of what is being observed. A recent study [63] conducted in Northeast China (121 • 30 20 E, 50 • 49 40 N, 845 m altitude) investigated the transmission of surface temperature changes to various soil depths. The results indicated that this transmission occurs within a specific time frame and with exponentially damped amplitudes.…”
Section: Discussionmentioning
confidence: 99%
“…[62] a high coefficient of determination (R 2 ) indicates high reliability and precision in the response of what is being observed. A recent study [63] conducted in Northeast China (121 • 30 20 E, 50 • 49 40 N, 845 m altitude) investigated the transmission of surface temperature changes to various soil depths. The results indicated that this transmission occurs within a specific time frame and with exponentially damped amplitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the early stage of post-fire recovery (1 year), the concentration of TP in the regenerating soils was relatively low. As secondary succession progressed following the fire disturbance, soil conditions favored an increase in species diversity, forest density and soil biomass, and vegetation flourish [45]. Consequently, there was an increase in the quantity of plant and animal residues entering the soil, contributing to the visible upward trend in soil fertility.…”
Section: The Trend For Tp During Different Restoration Periodsmentioning
confidence: 99%
“…Over the course of recent years, both climatic shifts and human interventions have been catalysts for substantial permafrost degradation in this specific region [23,25]. Such degradation is evidenced by changes in ALT, shifts in soil properties, modifications in microbial dynamics, and transitions in plant community patterns [26][27][28]. To delve deeper into the intricacies of N min fluctuations and their shaping factors, our team collected soil samples from stable, attached permafrost zones and from those showing signs of degradation.…”
Section: Introductionmentioning
confidence: 99%